MS-102 Microsoft 365 Administrator - Sequeira, Anthony; Goodwin, Sophia (Packt Publishing Ltd., 2024)
Dive into the comprehensive world of Microsoft 365 administration with this expertly crafted course. Begin with an overview and delve into deploying and managing a Microsoft 365 tenant. Learn to create and manage tenants and domains, monitor service health, and track adoption and usage. Master user, group, license, role, and privileged identity management, equipping you to handle bulk user management and delegation tasks efficiently. Next, explore implementing identity in Azure AD, a crucial skill for any Microsoft 365 Administrator. Utilize tools like IdFix and Azure AD Connect, synchronize directories, and troubleshoot authentication issues. Delve into advanced authentication methods, including multi-factor authentication and self-service password reset. Enhance security management skills with Microsoft 365 Defender. Improve the Microsoft Secure Score, respond to alerts, and handle security and compliance issues. Learn threat analytics, policy implementation, and using Defender for Office 365 and Endpoint. Finally, manage compliance with Microsoft Purview, handling sensitive information types, retention and sensitivity labels, and data loss prevention (DLP) across various workloads and endpoints.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Microsoft Office -- Study guides -- Examinations; Information technology -- Study guides -- Management -- Examinations; Microsoft software -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Technologie de l'information; Gestion; Examens; Guides de l'étudiant; Logiciels Microsoft; Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet